Preparation method of α-ZrP doped composite adsorption gel material and its heavy metal ion adsorption application

By introducing α-ZrP and CMC into starch-based hydrogels, the composite adsorption gel material is formed, which solves the problems of high production cost and poor adsorption performance of hydrogel materials, and achieves the effect of efficient adsorption of heavy metal ions.

CN118874425BActive Publication Date: 2025-03-21CHUZHOU UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411128214.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-16
Publication Date
2025-03-21
Estimated Expiration
2044-08-16

AI Technical Summary

Technical Problem

The existing hydrogel materials have high production costs and complex production processes, and the starch-based hydrogels have problems such as low adsorption and poor mechanical strength, which limits their practical application.

Method used

The two-dimensional layered nanomaterial α-ZrP is used as a filler, and sodium carboxymethylcellulose (CMC) is used in conjunction with the use of sodium carboxymethylcellulose (CMC) to improve the mechanical properties and adsorption properties of starch-based hydrogels to form an α-ZrP-doped composite adsorption gel material.

Benefits of technology

It improves the mechanical properties and adsorption properties of starch-based hydrogels, achieves efficient adsorption of heavy metal ions, and has high thermal stability and strong recyclability, reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118874425B_ABST
    Figure CN118874425B_ABST
Patent Text Reader

Abstract

The present invention discloses a preparation method of a layered α-zirconium phosphate (α-ZrP) doped composite gel material and its heavy metal ion adsorption application, which relates to the field of water pollution control. The purpose of the present invention is to solve the problems of low selectivity for copper ions, low adsorption capacity, poor mechanical strength, complex production process and high cost of existing copper ion hydrogel adsorbents. Method: (1) prepare a few layers or a single layer of α-ZrP powder filler; (2) add it to a gelatinized liquid of starch and sodium carboxymethyl cellulose (CMC); (3) add the mixed solution to a cross-linking solution for cross-linking; (4) crush it with a blender, soak it in ethanol, and vacuum dry it to obtain an α-ZrP doped composite gel material for use as a copper ion adsorbent, which has good mechanical strength and stability; for heavy metal copper ion adsorption, it has the characteristics of fast, high efficiency and high adsorption capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of water pollution control, and in particular to a preparation method of a composite gel material for removing heavy metal copper ions and its adsorption application. Background Art

[0002] With the development of economy, heavy metal ion wastewater pollution has become a major environmental problem, posing a great threat to the safety of ecosystems, animals and human life. At present, there are chemical precipitation, ion exchange, adsorption, membrane separation, biological treatment and other methods for the treatment of heavy metal ion wastewater. Among them, the adsorption method has the advantages of wide application range, fast reaction speed, simple treatment process and environmental friendliness, and has been widely used in water treatment. The selection and performance of adsorbents are the key factors that determine the treatment effect of adsorption method.

[0003] Compared with traditional adsorbents, hydrogels have unique advantages such as high adsorption capacity, fast adsorption speed, high reuse rate, and easy separation from water bodies, becoming a new hot spot in adsorbent synthesis research. Hydrogels can be divided into two categories: synthetic and natural hydrogels based on synthetic raw materials. Chitosan is one of the raw materials commonly used to synthesize natural hydrogels. It has certain adsorption properties. The amino group on its C2 has high reactivity and is easy to react with the crosslinking agent as a crosslinking point to form a chemical gel. However, the price of chitosan is relatively high, the production cost of chitosan-based hydrogels is high, and its adsorption performance is still inferior to that of synthetic hydrogels, which limits the practical application of this type of natural hydrogel. Starch is more widely available, cheaper, and completely biodegradable. The preparation of natural hydrogels using starch as raw material can effectively reduce production costs and improve the biodegradability of the product, which has great research value. However, the starch structure only contains hydroxyl groups, which are less reactive than the amino groups in chitosan, and starch itself does not have adsorption properties. This leads to the common disadvantages of low adsorption capacity, poor mechanical strength, and difficulty in recycling and reusability of starch-based hydrogels. Therefore, there is an urgent need in the art for a simple, convenient, eco-friendly and environmentally friendly starch-based composite hydrogel preparation method and product.

[0004] In recent years, nanomaterials have gradually emerged. Nanocomposite hydrogels can be prepared by introducing nanomaterials with special properties into polymer networks. This method does not change the properties of the polymer network itself and has mild preparation conditions. Therefore, it has attracted the attention of researchers. The introduction of nanomaterials has also made great breakthroughs in the limitations of traditional hydrogels. The unique organic (polymer) / inorganic (nanoparticle) network structure of nanocomposite hydrogels can simultaneously achieve multiple properties such as high mechanical strength, self-healing, and special stimulus response. Layered zirconium phosphate (α-ZrP) is a biocompatible nanomaterial that is often compounded with polymer matrix materials to improve the mechanical properties of the matrix. At the same time, α-ZrP is also an acidic two-dimensional layered ion exchange material with abundant surface hydroxyl groups, adjustable interlayer intermediates, high thermal stability and radiation stability, and effective ion exchange performance.

[0005] Most of the current hydrogel materials are made from non-renewable chemicals as raw materials, and the preparation process often requires the use of a large amount of organic solvents, such as dimethyl sulfoxide, glycerol ether, etc. This not only increases the preparation cost of the hydrogel, but also causes serious pollution to the environment, which is not conducive to its industrial application. Summary of the invention

[0006] The present invention provides a method for preparing a starch-based hydrogel and its heavy metal ion adsorption application, which solves the problems of high production cost and complicated production process of hydrogel to a certain extent. The two-dimensional layered nanomaterial α-ZrP is used as a filler to improve the mechanical properties of the starch-based hydrogel; at the same time, sodium carboxymethyl cellulose (CMC) is used in conjunction to further improve the adsorption performance of the starch-based hydrogel. In view of the common shortcomings of starch-based hydrogels, such as low adsorption capacity and poor mechanical strength, which lead to difficulty in recycling and reusability, the composite adsorption gel material doped with α-ZrP of the present invention improves the mechanical properties and adsorption properties of starch-based hydrogels, and has high thermal stability and strong recyclability.

[0007] To achieve the above object, the technical solution of the present invention is:

[0008] A method for preparing an α-ZrP-doped composite adsorption gel material is prepared by the following steps in sequence:

[0009] Step 1, dispersing α-ZrP powder in deionized water, ultrasonically dispersing, adding methylamine solution, and electromagnetically stirring evenly; then adding hydrochloric acid solution, stirring and centrifuging, washing with deionized water, and drying the solid to obtain a few-layer or single-layer α-ZrP powder filler;

[0010] Step 2, adding a few layers or a single layer of α-ZrP powder filler into starch and sodium carboxymethyl cellulose (CMC) gelatinized liquid, ultrasonically dispersing, and electromagnetically stirring to obtain a mixed solution;

[0011] Step 3, adding the mixed solution to the cross-linking solution, reacting in a nitrogen atmosphere to obtain a cross-linked hydrogel;

[0012] Step 4: Use a blender to break up the blocky hydrogel, wash it twice with deionized water to remove unreacted monomers, soak it with ethanol to remove moisture, and vacuum dry it to constant weight to obtain white α-ZrP-doped composite gel particles.

[0013] According to the preparation method of the present invention, preferably, the degree of substitution (DS) of sodium carboxymethyl cellulose in step (2) is 1.2, and the mass ratio of the few-layer or single-layer α-ZrP powder filler and sodium carboxymethyl cellulose to starch in step (2) is 0.005:0.5:1.

[0014] According to the preparation method of the present invention, preferably, in step 1, the molar ratio of methylamine to α-ZrP powder is (0.3-2.0):1, the molar concentration of the methylamine solution is 0.2 mol / L, and the solid-liquid ratio is controlled to be 10 g / L.

[0015] According to the preparation method of the present invention, preferably, in step 1, the molar ratio of hydrochloric acid to methylamine is 1:1, and the concentration of hydrochloric acid is 0.2 mol / L.

[0016] According to the preparation method of the present invention, preferably, in step 1 and step 2, the power of the ultrasonic dispersion is 300 W and the dispersion time is 15 min.

[0017] According to the preparation method of the present invention, preferably, in step 2, the mass ratio of the few-layer or single-layer α-ZrP powder filler and the sodium carboxymethyl cellulose to the starch is (0.005-0.02):0.5:1.

[0018] According to the preparation method of the present invention, preferably, in step 2, the degree of substitution (DS) of the carboxymethyl cellulose is 0.7-1.2.

[0019] According to the preparation method of the present invention, preferably, in step 2, the starch and cellulose microcrystals or carboxymethyl cellulose suspension are stirred at 90° C. for 10 minutes to obtain a gelatinized liquid, and the mixed liquid is cooled to room temperature for later use.

[0020] According to the preparation method of the present invention, preferably, in step three, the cross-linking solution is a sodium hydroxide solution of acrylic acid and N,N-methylenebisacrylamide with a neutralization degree of 60%, wherein the mass ratio of acrylic acid and N,N-methylenebisacrylamide to starch is 5:0.25:1.

[0021] According to the preparation method of the present invention, preferably, in step three, the cross-linking time is 3 hours and the cross-linking temperature is 75°C.

[0022] According to the preparation method of the present invention, preferably, in step three, the block hydrogel is soaked and washed with anhydrous ethanol for 3 times, and the soaking time is 2 hours.

[0023] According to the preparation method of the present invention, preferably, in step three, the vacuum drying temperature is 55-60° C., and after drying to constant weight, the mixture is cooled to room temperature for use.

[0024] Preferably, a method for preparing an α-ZrP-doped composite adsorption gel material comprises the following specific steps: (1) dispersing 1.0 g of α-ZrP powder in 91 mL of deionized water, performing ultrasonic dispersion at 300 W for 15 min, controlling the solid-liquid ratio to 10 g / L, the molar ratio of methylamine to zirconium phosphate to 0.5:1, adding 9 mL of 0.2 mol / L methylamine solution, and performing electromagnetic stirring to make the mixture uniform; after 30 min, adding 9 mL of 0.2 mol / L hydrochloric acid solution, stirring for 30 min, and then centrifuging, washing with deionized water, and drying the solid to obtain a few-layer or single-layer α-ZrP powder filler;

[0025] (2) Add 1.0 g corn starch and 0.5 g sodium carboxymethyl cellulose (DS=1.2) to 40 mL deionized water, stir evenly, gelatinize at 90° C. for 10 min, and cool to room temperature for later use;

[0026] (3) adding a few layers or a single layer of α-ZrP powder filler (0.5 wt %, based on the dry basis of starch) to the gelatinized liquid, and performing ultrasonic dispersion at 300 W for 15 min to obtain a mixed gelatinized liquid for later use;

[0027] (4) Add 9 mL of 5.0 mol / L NaOH solution to a mixed solution of 5 g acrylic acid and 0.25 g N,N-methylenebisacrylamide in an ice-water bath while stirring to obtain a crosslinking solution, which is kept at room temperature for later use; dissolve 0.06 g of ammonium persulfate in 5 mL of deionized water to obtain an initiator solution, which is kept for later use;

[0028] (5) adding the mixed solution to the cross-linking solution, adding the initiator solution and stirring evenly, reacting at 75° C. in a nitrogen atmosphere for 3 h to obtain a translucent gel;

[0029] (6) The blocky hydrogel was crushed using a blender, and then washed twice with deionized water to remove unreacted monomers, and then soaked in ethanol to remove water three times, each time for 2 hours. After solid-liquid separation, the mixture was placed at 60°C and vacuum dried to constant weight to obtain white granules, which was starch-based hydrogel, recorded as ZrP-0.5%-CMC-1.2.

[0030] In order to solve the technical problem of the present invention, another technical solution is proposed: the α-ZrP doped composite gel adsorption material is used as a copper ion adsorbent.

[0031] The application of the above-mentioned α-ZrP doped composite hydrogel in heavy metal ion adsorption, in a preferred case, is as follows: 0.03g of the above-mentioned ZrP-0.5%-CMC-1.2 doped composite hydrogel is stirred and mixed with 100mL of a 40mg / L heavy metal copper ion aqueous solution, adsorbed to equilibrium at 25°C, filtered, and the heavy metal ion concentration in the filtrate is determined by ultraviolet absorption chromatography; the obtained solid sample is the α-ZrP doped composite hydrogel after heavy metal ion adsorption. ZrP-0.5%-CMC-1.2 shows excellent removal effect, with an adsorption amount of 121.21mg / g and a removal rate of 91.0%.

[0032] Compared with the prior art, the present invention has the following advantages and beneficial technical effects:

[0033] (1) The raw materials of the present invention are starch, cellulose and their derivatives, which are widely available, inexpensive and suitable for large-scale industrial utilization.

[0034] (2) The preparation method of the hydrogel in the present invention is simple and green, does not use any organic solvent, and can be produced on a large scale.

[0035] (3) The α-ZrP doped in the present invention has good biocompatibility and rarely causes secondary pollution to the water environment during water treatment. The raw materials used are harmless to the human body and can be used for the adsorption and treatment of pollutants in drinking water.

[0036] (4) The introduction of the nanofiller α-ZrP in the present invention, with its large contact area between the layers and abundant hydroxyl groups (P-OH), can improve the secondary interfacial interaction by forming stronger hydrogen bonds and van der Waals forces, so that it plays a synergistic role in strengthening and toughening the starch matrix; at the same time, the ZrP / CMC hydrogel can adsorb heavy metal ions through chelation with various functional groups (-NH-, -C=O, -OH, -O-), thereby increasing the adsorption sites of heavy metal ions, enhancing the adsorption performance of metal ions, and having the advantage of high adsorption rate.

[0037] (5) After the composite adsorbent material adsorbs heavy metals, it can be washed with acid or alkali to elute the adsorbed pollutants, thereby regenerating the adsorbent material and then recycling it, thereby increasing the utilization rate of the material and reducing the development and use costs of the material.

[0038] (6) Figure 8 Schematic diagram of the difference in adsorption capacity of the composite hydrogels prepared in Examples 1 to 6, the adsorption conditions are: 0.03 g of each composite hydrogel, 100 mL of 40 mg / L copper ion solution, and 12 hours of adsorption time. Figure 8It can be seen that with the increase of α-ZrP, the 2+ Both the adsorption capacity and removal rate first increased and then decreased. The addition of α-ZrP affected the internal structure of the hydrogel and thus affected the adsorption effect. At the same time, it decreased with the decrease of the degree of substitution of CMC. That is, Example 2 (ZrP-0.5%-CMC-1.2) showed the best removal effect (adsorption amount of 121.21 mg / g, removal rate of 91.0%). BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 The infrared chromatograms of the composite hydrogels and raw materials prepared in Examples 2, 5, and 6 of the present invention; infrared spectra (a) corn starch, (b) sodium carboxymethyl cellulose DS = 0.7, (c) Example 6 (ZrP-0.5%-CMC-0.7), (d) Example 5 (ZrP-0.5%-CMC-0.9), (e) Example 2 (ZrP-0.5%-CMC-1.2).

[0040] Figure 2 This is the thermogravimetric diagram of the composite hydrogel ZrP-0.5%-CMC-1.2 prepared in Example 2 of the present invention;

[0041] Figure 3 The following are scanning electron micrographs of the composite hydrogel and raw materials prepared in Example 2 of the present invention; (a) α-ZrP, (b) sodium carboxymethyl cellulose DS = 1.2, (c) corn starch, (d) Example 2 (ZrP-0.5%-CMC-1.2).

[0042] Figure 4 is an X-ray diffraction diagram of the composite hydrogel and raw materials prepared in Example 2 of the present invention;

[0043] Figure 5 It is the N2 adsorption-desorption isotherm of the specific surface analysis (BET) of the composite hydrogel (ZrP-0.5%-CMC-1.2) prepared in Example 2 of the present invention;

[0044] Figure 6 Schematic diagram of the effect of pH on the adsorption capacity of the composite hydrogel prepared in Example 2 of the present invention;

[0045] Figure 7 is a Zeta potential diagram of the hydrogel prepared in Example 2 of the present invention at different pH values;

[0046] Figure 8Schematic diagram of the difference in adsorption amount of the composite hydrogels prepared in Examples 1 to 6 of the present invention; (a) ZrP-0-CMC-1.2, (b) ZrP-0.5%-CMC-1.2, (c) ZrP-1.0%-CMC-1.2, (d) ZrP-2.0%-CMC-1.2, (e) ZrP-0.5%-CMC-0.9, (f) ZrP-0.5%-CMC-0.7;

[0047] Fig. 9 This is a schematic diagram showing the effect of the dosage of the composite hydrogel prepared in Example 2 of the present invention on the adsorption capacity;

[0048] Fig.10 Schematic diagram of the effect of adsorption time on adsorption amount of the composite hydrogel prepared in Example 2 of the present invention;

[0049] Fig.11 This is a schematic diagram of the regeneration adsorption performance of the composite hydrogel prepared in Example 2 of the present invention.

[0050] Fig.12 Schematic diagram of the adsorption mechanism of the composite hydrogel prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0051] The technical scheme of the present invention is further described below by means of specific examples. Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.

[0052] Example 1

[0053] (1) Add 1.0 g corn starch and 0.5 g sodium carboxymethyl cellulose (DS=1.2, average MW250000, 1500-3100 mPa.s, purchased from Anage reagent, the same below) to 40 mL deionized water, stir evenly, gelatinize at 90°C for 10 min, and cool to room temperature for use; (2) Add 9 mL of 5.0 mol / L NaOH solution to a mixed solution of 5 g acrylic acid and 0.25 g N,N-methylenebisacrylamide in an ice-water bath while stirring to obtain a cross-linking solution, which is set aside at room temperature; dissolve 0.06 g ammonium persulfate in 5 mL of deionized water, to obtain an initiator solution for later use; add the mixed solution to the crosslinking solution, add the initiator solution and stir evenly, react at 75°C in a nitrogen atmosphere for 3 hours to obtain a translucent gel; (3) use a blender to break up the blocky hydrogel, soak it twice in deionized water to remove unreacted monomers, soak it in ethanol to remove moisture, place it at 60°C and vacuum dry it to constant weight to obtain a white granular substance, which is a starch-based hydrogel, recorded as ZrP-0-CMC-1.2. (ZrP-m-CMC-n, where m = 0, 0.5%, 1.0%, 2.0%, is the mass percentage of α-ZrP to starch; n = 0.7, 0.9, 1.2, is the degree of substitution of sodium carboxymethyl cellulose, the same below).

[0054] The adsorbent prepared in this example was ground into powder and used for evaluation of adsorption performance of copper solution.

[0055] 0.03 g of the composite hydrogel was stirred and mixed with 100 mL of a 40 mg / L heavy metal copper ion aqueous solution without adjusting the pH. After adsorption to equilibrium at 25° C., the mixture was filtered and the heavy metal ion concentration in the filtrate was determined by ultraviolet absorption chromatography. The obtained solid sample was the α-ZrP-doped composite hydrogel after the heavy metal ions were adsorbed.

[0056] Example 2

[0057] (1) 1.0 g of α-ZrP powder was dispersed in 91 mL of deionized water, and ultrasonically dispersed at 300 W for 15 min. The molar ratio of methylamine to α-ZrP was 0.5:1. 9 mL of 0.2 mol / L methylamine solution was added, and the solid-liquid ratio was controlled to be 10 g / L. Electromagnetic stirring was performed to make the mixture uniform. After 30 min, 9 mL of 0.2 mol / L hydrochloric acid solution was added. The mixture was stirred for 30 min and then centrifuged. The mixture was washed with deionized water and dried to obtain a few-layer or single-layer α-ZrP powder filler.

[0058] (2) Add 1.0 g corn starch and 0.5 g sodium carboxymethyl cellulose (DS=1.2) to 40 mL deionized water, stir evenly, gelatinize at 90° C. for 10 min, and cool to room temperature for later use;

[0059] (3) adding a few layers or a single layer of α-ZrP powder filler (0.5 wt %, based on the dry basis of starch) to the gelatinized solution of step (2), and dispersing them ultrasonically at 300 W for 15 min to obtain a mixed gelatinized solution for later use;

[0060] (4) Add 9 mL of 5.0 mol / L NaOH solution to a mixed solution of 5 g acrylic acid and 0.25 g N,N-methylenebisacrylamide in an ice-water bath while stirring to obtain a crosslinking solution, which is kept at room temperature for later use; dissolve 0.06 g of ammonium persulfate in 5 mL of deionized water to obtain an initiator solution, which is kept for later use;

[0061] (5) adding the mixed gelatinized liquid in step (3) to the cross-linking solution, adding the initiator solution and stirring evenly, reacting at 75° C. in a nitrogen atmosphere for 3 h to obtain a translucent gel;

[0062] (6) The blocky hydrogel was crushed by a blender, washed twice with deionized water to remove unreacted monomers, and then soaked in ethanol to remove water three times, each time for 2 hours. After solid-liquid separation, it was placed under vacuum drying at 60°C to constant weight to obtain white granules, which is the starch-based hydrogel, recorded as ZrP-0.5%-CMC-1.2. The adsorbent prepared in the above example was ground into powder and used for the evaluation of the adsorption performance of copper solution.

[0063] 0.03 g of the α-ZrP doped composite hydrogel was stirred and mixed with 100 mL of a 40 mg / L heavy metal copper ion aqueous solution, and adsorbed to equilibrium at 25°C without adjusting the pH, and then filtered. The heavy metal ion concentration in the filtrate was determined by spectrophotometry using a copper ion colorimeter, and the adsorption capacity and removal rate were calculated. The obtained solid sample is the α-ZrP doped composite hydrogel after adsorbing heavy metal ions.

[0064] Example 2 (ZrP-0.5%-CMC-1.2) showed excellent removal effect (adsorption amount of 121.21 mg / g, removal rate of 91.0%).

[0065] Table 1 is a comparative parameter table of the adsorption amount of copper ions by Example 2 of the present invention and different adsorbents;

[0066] Table 1 Effect of different adsorption agents on Cu 2+ The removal effect

[0067]

[0068] Example 3

[0069] (1) Disperse 1.0 g of α-ZrP powder in 91 mL of deionized water, and perform ultrasonic dispersion at 300 W for 15 min, control the solid-liquid ratio to 10 g / L, the molar ratio of methylamine to zirconium phosphate to 0.5:1, add 9 mL of 0.2 mol / L methylamine solution, and stir evenly; after 30 min, add 9 mL of 0.2 mol / L hydrochloric acid solution, stir for 30 min, and then centrifuge, wash with deionized water, and dry the solid to obtain a few-layer or single-layer α-ZrP powder filler; (2) Add 1.0 g of corn starch and 0.5 g of sodium carboxymethyl cellulose (DS=1.2) to 40 mL of deionized water, stir evenly, gelatinize at 90°C for 10 min, and cool to room temperature for use; add a few-layer or single-layer α-ZrP powder filler (1.0 wt%, based on starch dry basis) to the gelatinized liquid of step (2), 300W ultrasonic dispersion for 15min, to obtain a mixed gelatinized liquid, for use; (3) 5g acrylic acid and 0.25g N, N-methylenebisacrylamide mixed solution, stirring in an ice water bath while dripping 9mL of 5.0mol / L NaOH solution, to obtain a crosslinking solution, for use at room temperature; 0.06g ammonium persulfate was dissolved in 5mL deionized water to obtain an initiator solution, for use; the mixed solution was added to the crosslinking solution, the initiator solution was added and stirred evenly, and then reacted at 75°C in a nitrogen atmosphere for 3h to obtain a translucent gel; (4) The block hydrogel was crushed using a blender, soaked twice with deionized water to remove unreacted monomers, and then soaked with ethanol to remove moisture, and placed at 60°C and vacuum dried to constant weight to obtain a white granular substance, which is a starch-based hydrogel, recorded as ZrP-1.0%-CMC-1.2. The adsorbent prepared in the above embodiment was ground into powder for evaluation of copper solution adsorption performance.

[0070] 0.03 g of the α-ZrP doped composite hydrogel was stirred and mixed with 100 mL of a 40 mg / L heavy metal copper ion aqueous solution, and adsorbed to equilibrium at 25°C without adjusting the pH, and then filtered. The heavy metal ion concentration in the filtrate was determined by spectrophotometry using a copper ion colorimeter, and the adsorption capacity and removal rate were calculated. The obtained solid sample is the α-ZrP doped composite hydrogel after adsorbing heavy metal ions.

[0071] Example 4

[0072] (1) Disperse 1.0 g of α-ZrP powder in 91 mL of deionized water, and perform ultrasonic dispersion at 300 W for 15 min, control the solid-liquid ratio to 10 g / L, the molar ratio of methylamine to zirconium phosphate to 0.5:1, add 9 mL of 0.2 mol / L methylamine solution, and stir evenly; after 30 min, add 9 mL of 0.2 mol / L hydrochloric acid solution, stir for 30 min, and then centrifuge, wash with deionized water, and dry the solid to obtain a few-layer or single-layer α-ZrP powder filler; (2) Add 1.0 g of corn starch and 0.5 g of sodium carboxymethyl cellulose (DS=1.2) to 40 mL of deionized water, stir evenly, gelatinize at 90° C. for 10 min, and cool to room temperature for use; add a few-layer or single-layer α-ZrP powder filler (2.0 wt%, based on starch dry basis) to the gelatinized liquid of step (2), 300W ultrasonic dispersion for 15min, to obtain a mixed gelatinized liquid, for use; (3) 5g acrylic acid and 0.25g N, N-methylenebisacrylamide mixed solution, stirring in an ice water bath while dripping 9mL of 5.0mol / L NaOH solution, to obtain a crosslinking solution, for use at room temperature; 0.06g ammonium persulfate was dissolved in 5mL deionized water to obtain an initiator solution, for use; the mixed solution was added to the crosslinking solution, the initiator solution was added and stirred evenly, and then reacted at 75°C in a nitrogen atmosphere for 3h to obtain a translucent gel; (4) The block hydrogel was crushed using a blender, soaked twice with deionized water to remove unreacted monomers, and then soaked with ethanol to remove moisture, and placed at 60°C and vacuum dried to constant weight to obtain a white granular substance, which is a starch-based hydrogel, recorded as ZrP-2.0%-CMC-1.2. The adsorbent prepared in the above embodiment was ground into powder for evaluation of copper solution adsorption performance.

[0073] 0.03 g of the α-ZrP doped composite hydrogel was stirred and mixed with 100 mL of a 40 mg / L heavy metal copper ion aqueous solution, and adsorbed to equilibrium at 25°C without adjusting the pH, and then filtered. The heavy metal ion concentration in the filtrate was determined by spectrophotometry using a copper ion colorimeter, and the adsorption capacity and removal rate were calculated. The obtained solid sample is the α-ZrP doped composite hydrogel after adsorbing heavy metal ions.

[0074] Example 5

[0075] 1.0 g of α-ZrP powder was dispersed in 91 mL of deionized water, and ultrasonically dispersed at 300 W for 15 min, with the solid-liquid ratio controlled at 10 g / L and the molar ratio of methylamine to zirconium phosphate at 0.5:1. 9 mL of 0.2 mol / L methylamine solution was added, and electromagnetic stirring was performed evenly. After 30 min, 9 mL of 0.2 mol / L hydrochloric acid solution was added, and the mixture was stirred for 30 min and then centrifuged. The solid was washed with deionized water and dried to obtain a few layers or a single layer of α-ZrP powder filler. 1.0 g of corn starch and 0.5 g of sodium carboxymethyl cellulose (DS = 0.9, average MW250000, 1500-3100mPa.s, purchased from Anaiji reagent) was added to 40mL of deionized water, stirred evenly, gelatinized at 90°C for 10min, and cooled to room temperature for use; a few layers or a single layer of α-ZrP powder filler (0.5wt%, accounting for starch dry basis) was added to the gelatinized solution of step (2), and ultrasonically dispersed at 300W for 15min to obtain a mixed gelatinized solution for use; a mixed solution of 5g acrylic acid and 0.25g N,N-methylenebisacrylamide was added dropwise to a 5.0mol / L NaOH solution in an ice water bath while stirring. 9mL of liquid was added to obtain a crosslinking solution, which was set aside at room temperature; 0.06g of ammonium persulfate was dissolved in 5mL of deionized water to obtain an initiator solution, which was set aside; the mixed solution was added to the crosslinking solution, the initiator solution was added and stirred evenly, and then reacted at 75°C in a nitrogen atmosphere for 3h to obtain a translucent gel; the block hydrogel was crushed using a blender, soaked twice with deionized water to remove unreacted monomers, and then soaked with ethanol to remove moisture, and placed at 60°C to vacuum dry to constant weight to obtain a white granular substance, which is a starch-based hydrogel, recorded as ZrP-0.5%-CMC-0.9. The adsorbent prepared in the above embodiment was ground into powder for evaluation of the adsorption performance of copper solution.

[0076] 0.03 g of the α-ZrP doped composite hydrogel was stirred and mixed with 100 mL of a 40 mg / L heavy metal copper ion aqueous solution, and adsorbed to equilibrium at 25°C without adjusting the pH, and then filtered. The heavy metal ion concentration in the filtrate was determined by spectrophotometry using a copper ion colorimeter, and the adsorption capacity and removal rate were calculated. The obtained solid sample is the α-ZrP doped composite hydrogel after adsorbing heavy metal ions.

[0077] Example 6

[0078] 1.0 g of α-ZrP powder was dispersed in 91 mL of deionized water, and ultrasonically dispersed at 300 W for 15 min, with the solid-liquid ratio controlled at 10 g / L and the molar ratio of methylamine to zirconium phosphate at 0.5:1. 9 mL of 0.2 mol / L methylamine solution was added, and electromagnetic stirring was performed evenly. After 30 min, 9 mL of 0.2 mol / L hydrochloric acid solution was added, and the mixture was stirred for 30 min and then centrifuged. The solid was washed with deionized water and dried to obtain a few-layer or single-layer α-ZrP powder filler. 1.0 g of corn starch and 0.5 g of sodium carboxymethyl cellulose (DS=0.7, average MW250000, 1500-3100mPa.s, purchased from Anaiji reagent) was added to 40mL of deionized water, stirred evenly, gelatinized at 90°C for 10min, and cooled to room temperature for use; a few layers or a single layer of α-ZrP powder filler (0.5wt%, accounting for starch dry basis) was added to the gelatinized solution of step (2), and ultrasonically dispersed at 300W for 15min to obtain a mixed gelatinized solution for use; a mixed solution of 5g acrylic acid and 0.25g N,N-methylenebisacrylamide was added dropwise to a 5.0mol / L NaOH solution in an ice water bath while stirring. 9mL of liquid was added to obtain a crosslinking solution, which was set aside at room temperature; 0.06g of ammonium persulfate was dissolved in 5mL of deionized water to obtain an initiator solution, which was set aside; the mixed solution was added to the crosslinking solution, the initiator solution was added and stirred evenly, and then reacted at 75°C in a nitrogen atmosphere for 3h to obtain a translucent gel; the blocky hydrogel was crushed using a blender, soaked twice with deionized water to remove unreacted monomers, and then soaked with ethanol to remove moisture, and placed at 60°C to vacuum dry to constant weight to obtain a white granular substance, which is a starch-based hydrogel, recorded as ZrP-0.5%-CMC-0.7. The adsorbent prepared in the above embodiment was ground into powder for evaluation of the adsorption performance of copper solution.

[0079] 0.03 g of the α-ZrP doped composite hydrogel was stirred and mixed with 100 mL of a 40 mg / L heavy metal copper ion aqueous solution, and adsorbed to equilibrium at 25°C without adjusting the pH, and then filtered. The heavy metal ion concentration in the filtrate was determined by spectrophotometry using a copper ion colorimeter, and the adsorption capacity and removal rate were calculated. The obtained solid sample is the α-ZrP doped composite hydrogel after adsorbing heavy metal ions.

[0080] Figure 1 In the infrared spectrum, 1161cm -1 The absorption peak at 1078cm is the stretching vibration of CO and CC bonds; -1 The peak at 998cm is the bending vibration of the CH bond; -1 The asymmetric ring mode of starch is at 1603cm -1The symmetric and antisymmetric stretching vibrations of C=O are at 1724cm. In the spectrum of ZrP / CMC hydrogel, the skeleton vibration peak of the ring is further weakened. -1 1569cm -1 New absorption peaks appear at 1461cm and 1405cm, which are the stretching vibration of C=O and the bending vibration of NH. -1 The new peaks are the symmetric and asymmetric stretching vibrations of -COO-. The appearance of these new peaks indicates the presence of carbonyl, imino and carboxyl groups in the hydrogel structure.

[0081] Figure 2 In the thermal weight loss curve, there are three weight loss stages in the TG curve. The weight loss in the first weight loss stage (<230℃) is relatively small, and the loss is mainly various unbound water and bound water; the second weight loss stage (250℃-375℃) has obvious heat loss, which is caused by the disintegration of the cross-linked structure and the breakage of the starch molecular chain. The heat loss in the third stage (530℃-600℃) is due to the decomposition of the polymer side chain. The residual sample amount of hydrogel is 40.58%. Compared with starch (6.48%), the mass loss rate and total mass loss of hydrogel are smaller, which indicates that the thermal stability of hydrogel has been improved.

[0082] Figure 3 In the scanning electron microscope image, starch has a regular morphology, which is a spherical or polyhedral particle with a smooth surface; while CMC has no regular morphology, mainly composed of large rod-shaped particles and irregular debris; the crystal form of α-ZrP is relatively perfect, in the form of regular hexagonal flakes, with a grain diameter of about 1-3μm. In the ZrP / CMC hydrogel, the particles of starch and CMC disappear, the whole is in a block shape, and obvious holes appear. Generally speaking, the presence of a pore structure in the adsorbent is more conducive to adsorption.

[0083] Figure 4 In the X-ray diffraction pattern, compared with α-ZrP, starch and CMC, ZrP-0.5%-CMC-1.2 hydrogel has no obvious corresponding crystal diffraction peak, and only has an amorphous broad peak in the range of 2θ=18-24°. This is consistent with the hydrogels reported in most literatures.

[0084] Figure 5 The N2 adsorption-desorption isotherm of the hydrogel (ZrP-0.5%-CMC-1.2) prepared in Example 2 shows that the specific surface area of ​​the hydrogel is 0.3400 m 2 / g.

[0085] Figure 6 The effect of pH on adsorption of the hydrogel (ZrP-0.5%-CMC-1.2) prepared in Example 2 is shown in the graph. The corresponding pH is adjusted by hydrochloric acid and ammonia water.

[0086] Due to 40 mg / L Cu 2+ The solution itself is acidic, pH = 5.2. When pH = 5.5, some Cu 2+ Precipitation occurs, so the upper limit of the test is set at pH = 5.5. The hydrogel can maintain a high adsorption capacity in the range of pH = 3.5-5.5 and has strong acid resistance, but when the pH is less than 3.5, the adsorption capacity decreases significantly. This is mainly because when there is a large amount of H + When H + The ionization of the carboxylic acid group was inhibited, resulting in a decrease in the adsorption performance of the hydrogel.

[0087] Figure 7 Schematic diagram of the Zeta potential of the hydrogel (ZrP-0.5%-CMC-1.2) prepared in Example 2 at different pH values. The corresponding pH value was adjusted by hydrochloric acid and ammonia water. The Zeta potential decreased with increasing pH value (4-8); when pH>6, it dropped sharply; this is consistent with the adsorption capacity of the hydrogel at different pH values.

[0088] Figure 8 Schematic diagram of the difference in adsorption capacity of the composite hydrogels prepared in Examples 1 to 6, the adsorption conditions are: 0.03 g of each composite hydrogel, 100 mL of 40 mg / L copper ion solution, and 12 hours of adsorption time. Figure 8 It can be seen that with the increase of α-ZrP, the 2+ The adsorption capacity and removal rate both increased first and then decreased. The addition of α-ZrP affected the internal structure of the hydrogel and thus affected the adsorption effect. At the same time, it decreased with the decrease of the degree of substitution of CMC. That is, Example 2 (ZrP-0.5%-CMC-1.2) showed excellent removal effect (adsorption amount of 121.21 mg / g, removal rate of 91.0%).

[0089] Fig. 9 Effect of dosage of hydrogel (ZrP-0.5%-CMC-1.2) prepared in Example 2 on adsorption capacity, that is, without changing other adsorption conditions, only the dosage of hydrogel was changed, i.e., 0.01g, 0.02g, 0.03g, 0.04g and 0.05g. As the dosage of hydrogel increased, Cu 2+ The removal rate also gradually increased. When the dosage was 300 mg / L, the removal rate was 90.2%. The removal rate remained almost unchanged when the dosage was further increased. However, the adsorption amount showed a downward trend within the test range. This is mainly because when the dosage was small, the active adsorption sites on the hydrogel were occupied by Cu 2+ The occupancy rate is large and the adsorption capacity is large. However, the Cu 2+The number is limited. As the dosage increases, the occupancy rate of the adsorption sites decreases, resulting in a decrease in the adsorption amount.

[0090] Fig.10 Schematic diagram of the effect of adsorption time on the adsorption amount of the composite hydrogel prepared in Example 2. The adsorption equilibrium can be reached in about 30 minutes, and the adsorption rate is relatively high.

[0091] Fig.11 Example 2 Schematic diagram of hydrogel regeneration adsorption performance, that is, 40 mL of 0.2 mol / L hydrochloric acid solution is used as a desorbent to desorb the adsorbed hydrogel. After 4 adsorption-desorption cycles, the hydrogel has a good adsorption performance. 2+ The removal rate can still reach 76.1%, indicating that the hydrogel has strong regeneration performance.

[0092] Fig.12 Figure 2 is a possible adsorption mechanism diagram. On the one hand, the introduction of layered α-ZrP with abundant P-OH groups will improve the secondary interfacial interaction by forming stronger hydrogen bonds and van der Waals forces, thereby improving the mechanical properties of the composites; on the other hand, ZrP / CMC hydrogel can adsorb heavy metal ions through chelation with various functional groups (-NH-, -C=O, -OH, -O-).

[0093] The present invention is not limited to the specific technical solutions described in the above embodiments, and all technical solutions formed by equivalent replacement are within the protection scope required by the present invention.

Claims

1. A method for preparing an α-ZrP-doped composite adsorption gel material, characterized in that: The specific steps are as follows: (1) Disperse 1.0 g of α-ZrP powder in 91 mL of deionized water, and perform ultrasonic dispersion at 300 W for 15 min. Control the solid-liquid ratio to 10 g / L, the molar ratio of methylamine to zirconium phosphate to 0.5:1, add 9 mL of 0.2 mol / L methylamine solution, and stir evenly with electromagnetic stirring. After 30 min, add 9 mL of 0.2 mol / L hydrochloric acid solution, stir for 30 min, and then centrifuge. Wash with deionized water, and dry the solid to obtain a few-layer or single-layer α-ZrP powder filler. (2) Add 1.0 g corn starch and 0.5 g DS = 1.2 sodium carboxymethyl cellulose to 40 mL deionized water, stir evenly, gelatinize at 90 ° C for 10 min, and cool to room temperature for use; (3) Add a few layers or a single layer of α-ZrP powder filler with a starch dry basis accounting for 0.5 wt% to the gelatinized liquid, and disperse it ultrasonically at 300 W for 15 min to obtain a mixed gelatinized liquid for later use; (4) Add 9 mL of 5.0 mol / L NaOH solution to a mixed solution of 5 g acrylic acid and 0.25 g N,N-methylenebisacrylamide in an ice-water bath while stirring to obtain a crosslinking solution, which is set aside at room temperature; dissolve 0.06 g of ammonium persulfate in 5 mL of deionized water to obtain an initiator solution, which is set aside; (5) Add the mixed solution to the cross-linking solution, add the initiator solution and stir evenly, then react at 75°C in a nitrogen atmosphere for 3 h to obtain a translucent gel; (6) The blocky hydrogel was crushed using a blender, washed twice with deionized water to remove unreacted monomers, and then soaked in ethanol to remove water three times, each time for 2 hours. After solid-liquid separation, the mixture was placed at 60 °C and vacuum dried to constant weight to obtain white granules, which was the starch-based hydrogel, recorded as ZrP-0.5%-CMC-1.

2.

2. The adsorption application of the α-ZrP doped composite adsorption gel material prepared by the preparation method according to claim 1 is characterized in that: The α-ZrP doped composite gel adsorption material is used as a copper ion adsorbent.

Citation Information

Patent Citations

  • Preparation method and application of compound polysaccharide biomass gel adsorbent

    CN115155534A